PENERAPAN PENDEKATAN RME (REALISTIC MATHEMATICS EDUCATION) DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - lisa oktapia; Syarifah Yunus; Rora Rizky Wandini (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2022)
The purpose of this study is to provide knowledge on how the RME proximity method is still rarely used by educators, researchers use this approach method so that educators are easier to teach mathematics because this method uses a real medium and is close to the daily lives of students. The use of media or props in the RME approach is very important to bridge between the material in mathematics learning and the real life of the learner. The role of the teacher that is indispensable in this RME approach is as a facilitator and provides opportunities for students to explore more deeply about mathematics in their daily lives and students are required to be active together in carrying out the mathematics learning process.